EKSEKUSI HIPOTEK KAPAL LAUT SEBAGAI OBJEK JAMINAN PELUNASAN HUTANG PADA PERBANKAN - Daniel (Prodi Ilmu Hukum Fakultas Hukum Universitas Warmadewa, 2024)
This research aims to determine the problems surrounding the execution of mortgages on ships and the legal protection given to creditors (banks) when using ships as collateral for debt repayment. The actual document securing a debt claim is accompanied by a recorded or registered ship's mortgage, which constitutes substantial title to a ship. Although technically the ship is considered an immovable object in mortgage collateral, in practice it is more like a movable object that can be moved at any time. This created a problem because it was impossible to transfer the ship's mortgage. The implementation of Ship Mortgage Execution can be hampered by two principles, namely the Principle of Rijdende Beslag and the Principle of Freedom to Control and Use Ships. In accordance with the Rijdende Beslag principle, the debtor is allowed to store it and its facilities as long as it does not interfere with the defendant's interests or the ship's operations, both domestically and abroad. The application of these two principles makes conducting auction sales very challenging. The research method used is a normative juridical type with literature study. This research uses a comparative approach supported by primary legal materials in the form of Law Number 17 of 2008 concerning Shipping, the Commercial Code, the Civil Code, and HIR/RBG/Rv. Secondary materials include textbooks, legal dictionaries and journals. Research findings show that there are many ongoing problems related to the execution of mortgages on ships used as collateral for repayment of bank debts. In addition, the current legal framework does not comprehensively protect creditors with the certainty and security they need in collecting credit from financially indebted parties.